Field emergence of Marandu palisadegrass influenced by specific seed weight and sowing depth - Ricardo Fagundes Marques; Francielly Rodrigues Gomes; Cibele Chalita Martins; Sidnei Roberto de Marchi; Dagoberto Martins (Revista Ciência Agronômica)
ABSTRACT Several species of harmful grass weeds were voluntarily brought in by man, mainly with the specific purpose of produce forage. These species compete with crops for physical area and environmental resources, can host pests and diseases, and interfere on harvesting. This work aimed to evaluate in field conditions, the effects of different specific seed weight and sowing depths on the emergence of the species Urochloa brizantha cv. marandú. It was adopted a randomized blocks design with four replications and the treatments arranged in a 6 x 3 factorial scheme, with six sowing depths (1.0, 2.0, 4.0, 8.0, 12.0 and 16.0 cm) and three specific seed weight (low, medium, and high). The treatment effects were evaluated by seedling emergence in field. The marandu-grass seedlings emerged until 12 cm depth, regardless of specific seed weight and year. Sowing depths between 1.0 and 4.0 cm depth have promoted the greater percentage of emergence, and the lowest average time and speed index for emergence of seedlings on field, regardless of the specific seed weight. High-specific weight seeds resulted in greater percentage of emergence on field, speed and synchronicity index of emergence of marandú-grass seedlings. Sowing depths higher than 1.0 cm induces a delay on marandú-grass propagation.